2017
DOI: 10.7863/ultra.16.02078
|View full text |Cite
|
Sign up to set email alerts
|

Using Flow Characteristics in Three-Dimensional Power Doppler Ultrasound Imaging to Predict Complete Responses in Patients Undergoing Neoadjuvant Chemotherapy

Abstract: This preliminary study demonstrates the feasibility of using the vascular flow in breast tumors to predict chemotherapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was demonstrated that the most accurate prediction of pCR was achieved after the second chemotherapy treatment, with an accuracy of 88% and an AUC of 0.76. 80 The combined advantages of CEUS and 3D-US, 3D-CEUS, can evaluate tumor vascularity in a three-dimensional field. In Jia’s research, the 3D-CEUS score and DCE-MRI score were calculated according to the distribution and shape of breast tumor blood vessels in 3D-CEUS, and the enhancement pattern and index of tumor blood vessels in DCE-MRI, MVD and VEGF were also calculated.…”
Section: Three-dimensional (3d) Techniques For Assessing Response To Nacmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the most accurate prediction of pCR was achieved after the second chemotherapy treatment, with an accuracy of 88% and an AUC of 0.76. 80 The combined advantages of CEUS and 3D-US, 3D-CEUS, can evaluate tumor vascularity in a three-dimensional field. In Jia’s research, the 3D-CEUS score and DCE-MRI score were calculated according to the distribution and shape of breast tumor blood vessels in 3D-CEUS, and the enhancement pattern and index of tumor blood vessels in DCE-MRI, MVD and VEGF were also calculated.…”
Section: Three-dimensional (3d) Techniques For Assessing Response To Nacmentioning
confidence: 99%
“…© 2017 by the American Institute of Ultrasound in Medicine. 80 ⑥ Image of a responder case obtained by using ultrasound-guided diffuse optical tomography. ( A and B ) US images show US measuring a presize of 3.6 cm and a postsize of 0.7 cm in diameter.…”
Section: Other Us Techniques For Assessing Response To Nacmentioning
confidence: 99%
“…Blood perfusion variations evaluated by optical imaging show good predictive power regarding pCR to NACT in BC patients (17,19,21). The effect of chemotherapeutic drug may account for this finding, because the primary effect of most chemotherapeutic drugs is to shrink the tumor, disrupt microvessels, and decrease microvascular density (16,17). Therefore, for chemosensitive tumors, more total cells are killed and more tumor neovasculature damage occurs, which may cause a significant decrease in tumor hemoglobin measured by an optical imaging system (21).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis (or neovascularization), as another important factor in the tumor microenvironment, is considered a rate-limiting step in BC progression, and carries prognostic significance (13). Several imaging modalities yielding different imaging-derived hemodynamic parameters have been proposed for the assessment of tumor vascularity and the response to treatment (14)(15)(16)(17)(18)(19)(20)(21). However, dynamic contrast-enhanced magnetic resonance imaging (MRI), and positron emission tomography with computed tomography (PET-CT) have practical constraints, including cost, the use of contrast agents, and exposure to ionizing radiation from PET; in addition, these techniques are not feasible or are contraindicated in some patients, which limits the frequency of monitoring during treatment (16,17,19).…”
Section: Introductionmentioning
confidence: 99%
“…Two new studies which published recently represent that utilized the 3D-HDF US to quantify vascularity characteristics and identify differences associated with varying levels of chemotherapeutic response is possible [6,7]. These studies were focus to patients were stage T2 (tumor size 2 cm to 5 cm) under the estimate within tumor, node and metastasis (TNM) staging system according to the 6th AJCC [8], and receiving anthracycline-based therapies (FEC).…”
Section: Introductionmentioning
confidence: 99%